PENGARUH PROSEDUR DAN SISTEM INFORMASI AKUNTANSI TERHADAP PENGELOLAAN KAS DINAS PENDAPATAN KOTA MEDAN DILIHAT DARI ASPEK KEBIJAKAN - Tambunan, James Ronald; Dewi Sartika (Akademi Manajemen Informatika dan Komputer Widya Loka Medan, 2025)
This research is purposed to analysis partially and simultaneously influence of the policy, procedure and accounting information systems to the cash management effectiveness in Dinas Pendapatan Medan City. The sample method use are cluster random sampling method with 76 respondence by the 314 respondence and data process by using statistical test of multiple linier regression through SPSS 20. The result of this research are partially and simultaneously influence of the policy, procedure and accounting information systems to the cash management effectiveness in Dinas Pendapatan Medan City. The results of this study show that the effectiveness of cash management Effectiveness influenced by policies, procedures and accounting information systems. Partially only Procedure variables that significantly influence to the cash management effectiveness. This research suggesting policies, procedures and accounting information systems in eliminating errors in increasing the effectiveness of cash management. Keywords : Cash Management Effectiveness, Policy, Procedure and Accounting Information Systems.